Contemporary human resourse management issues in the construction industry - Leong, Peggy (2015)
The construction industry is one of the major sectors that has contributed to Singapore's successful transformation from a semi-rural entreport to a modern city-state with fine infrastructure and telecommunication networks. Like any other industry, the construction industry faces many external environmental problems such as those related to the labour force, society and government policies. Thus, to maintain competitiveness, the construction industry should adopt a well planned approach in utilising its resources; physical, human and financial efficiently and effectively. In view of its limited resources, there is the need for organisations and the government to pay more attention to developing and drawing the greatest potential in its workforce. The purpose of this project is to look into the critical human resource related issues prevalent in the construction industry, an industry which is a major employer of foreign workers. The issues will be addressed through an examination of some of the human resource functions, specifically Human Resource Planning, Recruitment, Employment Practices, Training and Development, Productivity, Compensation and Occupational Safety. The roles of the government bodies, and the private institutions in the construction industry are also discussed. The actors in the construction industry have been classified into four main groups namely: Construction Industry Development Board (CIDB), the statutory board that oversees the construction industry; Singapore Contractors Association Ltd. (SCAL), the voice channel for contractors; the Contractors themselves and; other Supporting bodies such as the Singapore Institute of Architects. General contractors and subcontractors are the main focus of analysis. A case study of one reputable local general contractor is discussed in Chapter 10. The construction industry's main concern is the prevailing labour shortage in all categories of staff The industry is heavily dependent on foreign workers to supplement the local workforce. With its existing poor image and the resultant difficulty in attracting locals in a period of high demand for construction output, companies in the industry will have to continually rely on foreign workers including professionals. However, in the long run through better integrated efforts by all actors in the construction scene, it is likely that the shortage problem will ease at least at the professional level. As more skilled foreign workers are granted permanent resident status and companies adopt advanced technology, it is likely that labour productivity will increase. With the trend of rising wages, particularly in the construction industry, at least an equal increase in productivity is necessary. CIDB plays an important role in training the workers. However, there is a need to provide greater awareness of the availability of co~rses and greater incentives must be given to attract the companies to release their workers for training. Continuous training for professionals should be emphasized and there must be greater enthusiasm to motivate the professionals in building a career and not just a job with the construction industry. Although the number of industrial accidents per million man hours worked in the construction industry is lower than the nation's average for the last five years, reflecting the sector's relatively higher safety consciousness, contractors should continue to uphold the philosophy "Safety starts with me" by adopting and implementing well devised safety programmes to achieve greater competitiveness.